Micro-atmospheres of place: light and dark on a modernist housing scheme. (January 2022) - May, Vanessa; Lewis, Camilla
This paper examines the role that light and dark play in how residents of Claremont Court, a modernist housing scheme in Edinburgh, Scotland, form a sense of atmosphere of place. Our findings show that the design of Claremont Court affords particular experiences of light and dark and of related warmth and cold that are meaningful to how residents experience and feel about the Court. While atmospheres tend to be conceptualised as spatially and temporally singular, our analytical focus on light and dark allows us to conceptualise the atmosphere of Claremont Court as made up of simultaneously held but distinct micro-atmospheres, which interact, overlap and even contradict each other. Furthermore, speaking to residents about their home environment revealed the role that memory plays in how people perceive atmosphere. Drawing from Mason's concept of socio-atmospherics, we theorise atmospheres not as spatially contained, but as trajectories through space, where the experience of atmosphere is one of intertwining (and at times contradictory) atmospheres past and present.